2013
DOI: 10.1002/ece3.532
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for male‐biased dispersal in theQinghai toad‐headed agamidPhrynocephalus vlangaliiand its potential link to individual social interactions

Abstract: Sex-biased dispersal has profound impacts on a species' biology and several factors have been attributed to its evolution, including mating system, inbreeding avoidance, and social complexity. Sex-biased dispersal and its potential link to individual social interactions were examined in the Qinghai toad-headed agamid (Phrynocephalus vlangalii). We first determined the pattern of sex-biased dispersal using population genetic methods. A total of 345 specimens from 32 sites in the Qaidam Basin were collected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…The total lake circumference is generally reported as around 360km (e.g., Virkutyte and Sillanpää, 2006) so our results suggest gene flow is sufficiently restricted to allow local divergence between populations separated by (on average) around 45 km. The closely-related P. vlangalii on the QTP also appears to show low dispersal, leading to detectable genetic structure (in microsatellites) over even shorter distances (20 km) (Qi et al, 2013). Other similar microsatellite studies of ectothermic vertebrates have detected isolation-bydistance over similar spatial scales (e.g., Arizona treefrogs; Mims et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…The total lake circumference is generally reported as around 360km (e.g., Virkutyte and Sillanpää, 2006) so our results suggest gene flow is sufficiently restricted to allow local divergence between populations separated by (on average) around 45 km. The closely-related P. vlangalii on the QTP also appears to show low dispersal, leading to detectable genetic structure (in microsatellites) over even shorter distances (20 km) (Qi et al, 2013). Other similar microsatellite studies of ectothermic vertebrates have detected isolation-bydistance over similar spatial scales (e.g., Arizona treefrogs; Mims et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…For example, in Lacerta , Olsson et al (1997) found that in both males and females, fitness was a strong component for dispersal and that males dispersed farther if relatedness was higher with respect to their neighbors. Similarly, Qi et al (2013) found clear genetic evidence of male-biased dispersal and strong female phylopatry in Phrynocephalus . In terms of female behavior, levels of aggression are higher in females with higher levels of paternity acquisition in the social lizard Egernia (While et al 2009).…”
Section: Discussionmentioning
confidence: 84%
“…Further, male-biased dispersal favors mitochondrial genome introgression ( Toews & Brelsford, 2012 ) and Phrynocephalus appears to have male-mediated gene flow. Discordant breaks in mtDNA and nuDNA markers occur in at least for four species: Phrynocephalus vlangalii – Phrynocephalus putjatai Bedriaga, 1909-groups ( Noble, Qi & Fu, 2010 ; Qi et al, 2013 ), and in the P. przewalskii–P. frontalis -groups ( Urquhart, Wang & Fu, 2009 ).…”
Section: Discussionmentioning
confidence: 99%